MAMPUKAH PDB HIJAU MENGAKOMODASI DEGRADASI LINGKUNGAN DAN KESEJAHTERAAN MASYARAKAT? - ., Suryanto (Jurnal Ekonomi & Studi Pembangunan, 2009)
Economic theories, especially theories of development evolves from the Gross Domestic Product (GDP) to the sustainable economic development. But the scenario toward economic sustainability is still characterized various opinions on the implementation of green GDP. There is the notion that environmental impacts will be reduced automatically if the level of public welfare has been achieved. While other opinion says that there is no positive relationship between economic growth by improving environmental quality. This paper presents the arguments of these two opinions. This paper concludes with reviews of green GDP concept is associated with environmental degradation, and welfare of the community. Green GDP growth rates have economic consequences that low since corrected by environmental constraints. However, improved environmental quality and provide hope for humans to live sustainable. Problem that must be addressed along with the implementation of green GDP is to do redefinition of welfare.Â